An Aminoantipyrine-containing Schiff base Fluorescent Chemosensor for Hg2+-Selective Detection - He, Xuelei; Song, Shijie; Li, Chengke; Zhang, Qiangqiang; Dong, Qiang; Li, Lin; Qin, Yonggang; Zhao, Qiang; Wang, Jianxiong (Letters in Organic Chemistry, 2023)
Specific recognition at trace quantity levels of metal ions without using the costly analytical instrument and a tedious sample preparation method is an extensive concern for environmental monitoring and mitigation. Mercury(II) (Hg2+) has acute toxicity. The development of ion-selective fluorescence sensors for the selective detection of Hg2+ is an essential task to accomplish. The aim of this study is to detect Hg2+ in an aqueous medium. A fluorescence sensor (DP) based on Schiff base was designed and utilized to detect Hg2+. Scanning electron microscope (SEM), Fourier transformed Infrared (FT-IR), X-ray powder diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) were used to learn the sensing mechanism between sensor DP and Hg2+ cations. When Hg2+ ions were added to the sensor DP, it showed a dramatic fluorescent “turn-on” response for Hg2+ in dimethylformamide (DMF) solution. And the detection limit (LOD) of DP for Hg2+ in aqueous media (1.0 mol L-1) was 2.23 × 10-8 mol L-1. In summary, an aminoantipyrine-containing Schiff base fluorescent chemosensor for extraordinary recognition of Mercury(II) was designed and synthesized via a simple one-step pathway and led to intermolecular self-assembly through π-π stacking interactions. And the sensor DP could fluorescently “turn on” when the Hg2+ cation was added. The limitation of Hg2+ was 2.23×10-8 M, which indicated that the sensor DP could be useful as a highly selective and sensitive sensor for detecting Hg2+ ions in an aqueous medium by the strong interaction with DP. Notably, the sensor DP was used as a fluorescent display material with satisfactory results.
Keywords: metal ion recognition